2019
DOI: 10.1352/1934-9556-57.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Medicare Beneficiaries With Intellectual or Developmental Disabilities

Abstract: Gaps in knowledge and systematic tracking of the prevalence of intellectual and developmental disabilities (IDD) and characteristics that may affect the health of this disability group limits our ability to address the health disparities they experience in comparison to people without disability. The purpose of this study is to begin to fill one relevant critical gap in knowledge: understanding the demographics and health outcomes of adults with IDD who receive services under Medicare Fee-for-Service (FFS), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…inequities in patterns of health care use, including overreliance on the emergency department as a source of care for people with intellectual disability (Hosking et al, 2017;Reichard et al, 2019).…”
mentioning
confidence: 99%
“…inequities in patterns of health care use, including overreliance on the emergency department as a source of care for people with intellectual disability (Hosking et al, 2017;Reichard et al, 2019).…”
mentioning
confidence: 99%
“…While food insecurity negatively harms the physical and mental health of everyone, 1 , 2 , 3 , 4 , 5 , 6 , 7 it may be particularly harmful for PWD who were Medicare beneficiaries who are already vulnerable, underserved, and have multiple chronic conditions. 26 , 27 , 33 , 34 , 35 , 36 , 37 A multipronged approach to food insecurity that addresses public health and other systems and structures, ranging from disability services to discrimination, is critical. 2 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…First, existing studies primarily focus on single outcomes and single healthcare sectors. One exception is a study by Reichard et al, 8 which reported higher proportions of frequent emergency department use, repeat hospital admissions and mortality in adults with IDD relative to other Medicare recipients in the USA. Second, published studies often use the entire general population as is, or control for age and gender, but not morbidity, when conducting comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general population, they are more likely to reuse in-patient and emergency department services, often within 30 days of a previous discharge or visit, suggesting insufficient support for managing their health issues in the community after discharge. 7,8 Once in hospital, they are more likely to remain despite being deemed ready for discharge. 9 They are also more likely to be admitted into long-term care (LTC) facilities at a younger age, 10 and to die earlier.…”
Section: Introductionmentioning
confidence: 99%